EDUCATION OF PATIENTS WITH STAGE I CHOLELITHIASIS AT THE HEALTH SCHOOL - N. A. Khokhlacheva; O. D. Mikhaylova; A. V. Bystrova (SINAPS LLC, 2019)
The education of patients at the health school with the objective to improve the effectiveness of treatment of cholelithiasis and to prevent the gallstone formation was organized.Material and methods. 210 patients with cholelithiasis, stage I, were examined: 123 patients (the follow up group) received therapy due to medical and economic standards and were educated in the health school; 87 patients (the comparison group) received only standard therapy. The examined groups of patients were balanced by gender and age. In verification of the diagnosis, in addition to general clinical data, the results of ultrasound examination of the gallbladder were used. The study of psycho-emotional state, health literacy and medical activity dynamics was performed during treatment. The criteria for evaluating of the effectiveness of education at health school were the results of responses to tests and questionnaires.Results. All patients had abdominal pain and dyspeptic syndromes. The study of psychoemotional status revealed significant increasing of state and trait anxiety and the level of depression. The inclusion of health education in the treatment regimen contributed to a distinct decrease of anxiety, that indicates the normalization of the psycho-emotional status, and leads to the more significant positive dynamics of clinical signs. Gaining additional knowledge about cholelithiasis and its prevention contributed to the  increase of patient's motivation to follow the recommended procedures, diet and rational physical activity.Conclusion. The use of the developed structured program of active education of patients with the cholelithiasis, stage I, as part of complex therapy contributes to the improvement of the therapeutic effect, i.e. the earlier decrease of pain and dyspeptic syndrome, and restoring of psycho-emotional balance. After educational classes, the increase of health literacy, medical activity, motivation to maintain health-preserving behavior was revealed, which lasted for 1 year. Thus, the therapeutic education of patients at the early stage of cholelithiasis in health school is clinically confirmed and promising for the prevention of this disease.